A new species of Microprosthema Stimpson, 1860 (Crustacea: Decapoda: Stenopodidea: Spongicolidae) from the South China Sea - Jiang, Qiwu; Li, Xinzheng (Zootaxa, 2014)
A new species of the spongicolid genus Microprosthema Stimpson, 1860 is described based on two specimens collected from Shi Island, Xisha Islands, South China Sea. The type specimens were collected within a sponge, representing an unusual habitat for the genus. M. personatum sp. nov. is easily distinguished from its closest congeners, M. takedai and M. fujitai, by its convex supraocular eaves and the number of teeth on the scaphocerite. A key to the Indo-West Pacific species of Microprosthema is given.